27th SEPTEMBER 2015 CATALAN PARLIAMENTARY ELECTIONS AND THE INDEPENDENCE PROJECT - MIGUEL A. Ruiz De Azúa (Ибероамериканские тетради, 2016)
The article studies the parliamentary elections in Catalonia on 27th if September 2015, which were po-sitioned by the separatist forces as a referendum on the partition of this autonomous region from Spain. The author analyzes the standpoints of various political forces participating in the elections and the election results.